Linear polarization properties of energetic x-rays being Compton-scattered off atomic targets - W Middents; A Gumberidze; T Krings; T Over-Winter; P Pfäfflein; N Schell; U Spillmann; M Vockert; G Weber; Th Stöhlker (New Journal of Physics, 2025)
We perform a study on the Compton scattering of a photon beam off atomic targets. The main focus of this study is the influence of the momentum distribution of the target electrons on the polarization transfer in Compton scattering from the incident to the scattered photons. For this purpose we developed a Monte Carlo simulation of the Compton scattering process based on the relativistic impulse approximation. This simulation provides information on the double differential scattering cross section as well as the linear polarization of the scattered radiation over the entire energy range of the Compton peak for arbitrary incident linear polarization characteristics. Furthermore, we compare the predictions yielded by the simulation to data obtained in an experiment where a highly linearly polarized hard x-ray beam with a photon energy of 175 keV was scattered off a thin gold foil target. Both the simulation as well as the experimental results suggest a deviation of the linear polarization of the scattered radiation at the center of the Compton peak compared to scattering off a free electron at rest and a change of the polarization over the Compton peak due to the influence of the initial electron momentum.